Enhancing the Mechanical Characteristics of the Traditional Concrete with the Steel Scrap. Issue 1 (1st July 2022) - Venugopal, N; Emmanual, L; Sunagar, Prashant; Parida, Lukesh; Sivaranjani, M.; Santhanakrishnan, M.
Abstract: The mechanical performance of concrete with varying proportions of steel scraps as a composite additive is investigated in this work. A M50 grade concrete admixture with a 0.35 water-to-binder ratio was prepared for this study. The appropriate quantity of superplasticizer was included as the mineral admixture. Steel scraps are obtained as waste from local machining workshops and then included in various proportions, including 0.25, 0.5, 1.0, and 2.0 percentages. The cubical mortar specimens were being employed to determine the compressive characteristics of mortar structure with and without steel scrap, whilst the cylinder-formed specimens and beam shaped samples were being utilized to determine the indirect tensile strength and flexural strength of concrete mixture. All experiments with different percentages of steel scrap were conducted on the 3 replicates, and the mean value is provided in this paper. After 28 days, the cement without steel scrap seemed to have a mean compression, flexural, and tensile strengths of 46.3 MPa, 5.52 MPa, and 4.23 MPa, respectively, which were improved to 51.7 MPa, 6.16 MPa, and 4.58 MPa with the inclusion of 1.0% steel scrap. The proposed investigation will contribute to reducing cement use, hence reducing cement industry's adverse ecological impacts.